Dynamic depositor discipline in US banks - Maechler, Andrea M.; McDill, Kathleen M. (Journal of Banking & Finance, 2006)
This paper captures banks’ dynamic response to depositor discipline. Recognizing that the price and quantity response of uninsured deposits in the face of deteriorating fundamentals needs to be modeled as an endogenous process, we investigate how depositor discipline constrains banks’ behavior by extracting the impact of an exogenous rise in interest rates on the quantity of uninsured deposits. We find that good banks can raise uninsured deposits by raising their price, while weak banks cannot. This suggests that depositor discipline not only raises the cost of choosing a higher level of risk but also may, at very high levels of risk, effectively constrain bank managers’ behavior.